Filsafat Hukum dalam Putusan Mahkamah Agung: Studi atas Pembagian Harta Bersama Suami Istri - Musthofa, Moh Aqil (UIN Sunan Kalijaga, 2018)
Abstract: Ideally, a judgment must meet the principles of certainty, fairness and usefulness. However, in fact it has been far from easy to synchronize between the whole three principles, especially when it comes to the principle of certainty and fairness, which may conflict with each other. Supreme Court (MA) Decision No. 266/K/AG/2010 indicates that in terms of cases of marital assets, the Panel of Judges did not determine their judgment based on the material legal provisions of Article 97 KHI. This fact raises the following question: what is the legal paradigm, legal formation or discovery, and legal value in the Supreme Court decision No. 266/K/AG/2010? To analyze these three aspects, the researcher used progressive legal theory, maqāṣid asy-syari’ah, and legal ideals theory. From the study and analysis, it is possible to conclude the following points. First, in terms of the legal aspect, this decision is intended for the sake of humans. It was aimed to satisfy the principle of fairness, prosperity and happiness for both parties. Second, the decision indicates that the Panel of Judges made legal discovery to meet the objectives of Islamic law (maqāṣid asy-syari’ah) of creating benefits for both parties. Third, the legal decision constitutes the principles of legal certainty, legal justice, and legal benefits for both parties.Abstrak: Putusan hakim di pengadilan, idealnya, harus mengandung nilai kepastian, keadilan, dan kemanfaatan. Dalam implementasinya, tidak mudah untuk mensinergikan ketiga nilai tersebut, terutama nilai kepastian dan keadilan yang terkadang saling bertentangan. Putusan Mahkamah Agung No. 266/K/AG/2010 mengindikasikan bahwa Majelis Hakim dalam memutus perkara pembagian harta bersama suami-istri tidak mendasarkan pada ketentuan hukum materiilnya, yaitu Pasal 97 KHI. Sesuai fakta tersebut, maka muncul pertanyaan: bagaimana paradigma hukum, pembentukan atau penemuan hukum oleh Majelis Hakim, serta nilai hukum dalam putusan No. 266/K/AG/2010. Tulisan ini mendeskripsikan: pertama, aspek ontologi untuk mengetahui hakikat hukum; kedua, aspek epistemologi untuk mengetahui prosedur penemuan atau pembentukan hukum; ketiga, aspek aksiologi untuk mengetahui nilai-nilai hukum. Teori hukum progresif, maqāṣid asy-Syari’ah, dan teori cita hukum digunakan dalam tulisan ini untuk menganalisis ketiga aspek tersebut. Kesimpulan dari tulisan ini: pertama, hakikat hukum dalam putusan ini adalah untuk manusia, putusan ini ditujukan untuk kedua pihak agar mendapat keadilan, kesejahteraan, dan kebahagiaan; kedua, Majelis Hakim melakukan penemuan hukum berdasarkan Maqāṣid asy-Syari’ah, yang mempertimbangkan kemaslahatan; ketiga, putusan tersebut telah mengandung nilai kepastian hukum, keadilan hukum, dan kemanfaatan hukum bagi kedua pihak.